Motivation and self-esteem in university students’ adherence to physical activity (2015)
Objective This study aimed to determine the association between motivation, self-esteem and body composition in university students' adherence to physical activity.Methods A total of 110 undergraduates from two public universities (Federal and State) in Teresina, Piauí state volunteered for the study. Of these, 75 (68.2 %) were women aged between 18 and 35 years, and 82 (74.5 %) of the students engaged in physical activity. They responded to the Gonçalves Motivation Scale (2010), which contains five factors: Fun, Competency, Appearance, Health and Sociability. Participants also completed the Lages Self-esteem Scale, with sixteen items and five dimensions: Introspection, Physical Image, Life Satisfaction, Acceptance and Confidence. The Jackson and Pollock (1978 and 1980) 3-site skinfold protocol was used to measure fat percentage and body composition by anthropometry (Filizola scale equipped with stadiometer).Results A significant association between the variables of self-esteem and motivation was demonstrated, with the physical image dimension exhibiting the highest association with the motivational factors fun, competency and sociability. Conclusion The findings indicate that adherence to physical activity is associated to motivational factors derived from challenging, integrative and fun-related circumstances.